The Academic language of climate change : an introduction for students and non-native speakers - Manolas, Evangelos I.; Leal Filho, Walter (Emerald Publishing Limited, 2022)
Climate change is one of the greatest challenges of our time. For the sake of human civilization and life on earth we must do all we can to keep global warming at the lowest possible level. Addressing climate change is everyone's duty and that includes teachers of English. In order to support students and non-native English speakers, this important work provides an introduction to climate change via simple chapters addressing different and important dimensions of climate change and helps students acquire basic language skills which will allow them to study similar or more difficult texts. Each chapter offers an introduction on the topic discussed and its relation to climate change, outlines climate change or other related environmental science terms and 6-8 exercises on grammar, syntax and consolidation of terminology. Topics covered include climate change and tourism, gender, worker safety, mental and physical health, food production, deforestation, art, and much more. Offering an interdisciplinary introduction to climate change and its intersection with numerous industries and facets of life, The Academic Language of Climate Change, provides a necessary and welcome introduction for undergraduate and graduate students, and any non-native English speakers seeking to engage with climate change research.
Keywords: Climatic changes -- Study and teaching (Higher); Academic language -- Study and teaching (Higher) -- Foreign speakers.; English language -- Study and teaching (Higher) -- Foreign speakers.; Language arts -- Correlation with content subjects.; Education -- Teaching Methods & Materials / Science & Technology.; Climate change.; elektronické knihy; electronic books